Stereoselective effects of monoterpenes on the microviscosity and curvature of model membranes assessed by fluorescence anisotropy and light scattering analysis. - Zunino, María Paula (2011)
Here, we evaluated stereoselectivity in monoterpenes (MTs) ability to disturb membrane dynamics. Correlations between molecular structure and physicochemical properties of pinenes, menthols, and carvones enantiomers were investigated through cluster and principal component analysis. Therefore, MTs' concentration-dependent changes in light scattering and diphenylhexatriene (DPH) fluorescence polarization induced by MTs were measured on large unilamellar vesicles (LUVs) of dipalmitoylphosphatidylcholine. The behavior of the less polar compounds (hydrocarbons) was characterized by a membrane expansion (increase in light scattering), detectable within the low-concentration range. They remained in the membrane up to the highest concentrations tested exhibiting a concentration-dependent anisotropy decrease. Within the more polar terpenes (alcohols) prevailed a budding phenomenon with the production of small LUVs with roughly constant curvature (more evident at medium and high concentrations), which explains the slight change in microviscosity (DPH fluorescence anisotropy). These behaviors were compatible with the deeper localization within the membrane core of the formers compared with the latters as predicted from the corresponding polar charge distribution in their molecular structures. The enantioselectivity was expressed by neomenthol at low concentration and carvone at medium concentration. Inhibition and potentiation were evidenced, within the low-concentration range, by the racemic mixtures in neomenthol and β-pinenes, respectively.